Ludicidade, animação cultural e educação : um olhar para o projeto "Vivências em atividades diversificadas de lazer" - Santos, Matheus Oliveira (Universidade Federal de São Carlos, 2008)
The present study was developed in Jardim Gonzaga , a peripheral neighborhood of the city of São Carlos, interior of the State of São Paulo, where the project Vivências em Atividades Diversificadas de Lazer (Experiences in Diversified Leisure Activities) takes place. This is a university extension project (São Carlos Federal University), in partnership with the project Campeões na Rua (Champions in the Street), coordinated by São Carlos s Town Hall. The objective of this research was to analyze the educative processes present in the social practice of leisure, with particular attention to the playful elements (ludic), in the context of the project Vivências em Atividades Diversificadas de Lazer , which took place in the Communitarian Station (ECO) of Jardim Gonzaga, especially through the perception of the oldest participants, their relatives and the educators. The methodology used was situated phenomenon , a phenomenological qualitative inquiry. Interviews were carried out with four participants and four respective relatives¸ inserted in the projects since the beginning (2002). Three educators currently participating in the project were also interviewed. For the gathering of data, field diaries were made between September of 2004 and April of 2008. In the analysis of the data the next categories were established: A) Playing and learning in the project; B) ECO is a better space for the projects; C) The importance of the educators; D) Driving children out of the street; E) To play and to learn with a full tummy is better. These categories made the construction of the results possible. In the considerations I observed, among the educative processes resulting from the relationship between the participants, the educators and their relatives: learning while they are playing, diversified ludic experiences and independence in choosing how to enjoy leisure, affection and sensibility, collective work, respect and solidarity for others, racial-ethnically affirmative actions, respect and interaction with the environment, incentive towards reading and writing, apprenticeships in different spaces, commitment. Finally, I would like to emphasize that besides what we learn (games; mutual respect, without regard to gender, age, race, social status, professional status, culture...), equally important is how we learn (we humanize ourselves): in concrete experiences, in significant existences, in reciprocity.
Keywords: Educação; Práticas sociais e processos educativos; Lazer; Ludicidade; Animação cultural; Educative processes; Leisure; Ludic; Cultural liveliness; Education.; CIENCIAS HUMANAS::EDUCACAO